2004
DOI: 10.1016/s0210-4806(04)73107-1
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento con sildenafilo del síndrome de glande frio tras implante de prótesis hidráulica de pene

Abstract: Sildenafil could be used to improve functional results of the penile prosthesis in those patients with CGS and seems to increase satisfaction during SI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…[30] found that most patients responded to sildenafil and reported higher satisfaction than with an implant alone. Lledo et al [31] have also reported similar results.…”
Section: Surgical Pitfalls and Specific Considerationssupporting
confidence: 60%
See 1 more Smart Citation
“…[30] found that most patients responded to sildenafil and reported higher satisfaction than with an implant alone. Lledo et al [31] have also reported similar results.…”
Section: Surgical Pitfalls and Specific Considerationssupporting
confidence: 60%
“…When ED causes depression, it is postulated that the causes include anxiety regarding sexual function, poor self-image, and poor self-esteem. [3132] Seidman et al . reported that men with ED had high frequency of depressive, somatic, and anxiety symptoms and scored very high on measures of overall psychological distress.…”
Section: Psychological Aspects Of Penile Prosthesismentioning
confidence: 99%
“…Efforts have been made to preserve some postoperative residual erectile function in the form of spontaneous tumescence and increased penile girth during sexual activity, which may play an important role in inciting female arousal [ 7 , 8 ]. Therefore, PDE5i were prescribed after penile prosthesis implantations to increase patients' and partners' satisfaction by enhancing glans engorgement [ 9 , 10 ]. In that context, Mulhall et al [ 11 ] pointed out that patient satisfaction was indeed significantly increased with the implant-PDE5i combination compared to the implant alone.…”
Section: Introductionmentioning
confidence: 99%